2017
DOI: 10.1016/j.jiph.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of Chinese herb residues using probiotics and evaluation of their beneficial effect on pathogen infection

Abstract: Environmental pollution caused by herb residues and the huge waste of medicinal ingredients contained in herb residues hinder the development of traditional Chinese medicine enterprises. To solve this problem, several probiotics were tested, and Lactobacillus plantarum (HM218749) was finally selected for the reuse of herb residues of Jianweixiaoshi tablets. A mouse model of Helicobacter pylori infection was developed to evaluate the anti-H. pylori infection activity of the herb residue fermentation supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…The majority of these used materials are stacked in the open, buried, or burned, thereby affecting the surrounding environment. 1 Thus, various approaches for utilizing these discarded materials, including composting and vermicomposting, pyrolysis, use of feed additives and biosorbents, and propagation of edible fungi, have been evaluated. 2,3 Mushroom cultivation can biodegrade industrial waste and transform it into proteinaceous food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these used materials are stacked in the open, buried, or burned, thereby affecting the surrounding environment. 1 Thus, various approaches for utilizing these discarded materials, including composting and vermicomposting, pyrolysis, use of feed additives and biosorbents, and propagation of edible fungi, have been evaluated. 2,3 Mushroom cultivation can biodegrade industrial waste and transform it into proteinaceous food.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Herb residues are the resulting by-products of extraction of traditional Chinese medicinal materials using ethanol or water, and thus may still contain 30-50% of the various active substances. 1 During mushroom cultivation, certain bioactive ingredients are effectively absorbed by the fruiting bodies of Pleurotus. 10 However, studies of the chemical components and therapeutic value of the herb-supplemented mushrooms are limited.…”
Section: Introductionmentioning
confidence: 99%
“…This results in an increased yield in Chinese herbal medicine residue. Moreover, due to poor extraction processes and extraction e ciency, the herbal residue still contains nutrients such as cellulose, hemicellulose and lignin, as well as 30% − 50% medicinally active ingredients (Wang et al, 2010;Meng et al, 2017). For example, the contents of calycosin and formononetin in Radix Astragali residue were 75.16% and 77.06%, respectively (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2016) suggested that Astragalus residue improved the immunity and digestion ability of white ducks resulting in a corresponding increase in body weight and weight of immune organs. In another study, it was shown that herbal residue fermentation supernatant (Jianweixiaoshi tablets) inhibits urease activity, slows down cell in ltration in the gastric area, reduces the level of gastric in ammatory cytokines IL-6, IL-8 and TNF-α, and helps to improve a disturbed microbiota, indicating strong potential in treating Helicobacter pylori infections (Meng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Jianweixiaoshi tablets have been demonstrated to promote gastrointestinal peristalsis and gastric secretion of digestive juices, and enhance the activity of pepsin, general physique and immune function (7). In China, sales of Jianweixiaoshi tablets generate >1.2 billion renminbi in income each year, although they also produce ~100,000 tons of herb residues which are primarily used in food additives (7,8).…”
Section: Introductionmentioning
confidence: 99%